MODERN MICROCONTROLLERS IN SCHEMES OF ROLLING STOCK - Ustymenko, D. V. (Science and Transport Progress, 2007)
General structure of a microcontroller has been presented; the basic requirements to it and its peripheral modules have been formulated in case of their use in the systems of automated control of rolling stock. An analysis has been executed and a perspective structure of modern control systems on the basis of microcontroller equipment has been identified.